DIY radar system - Tan, Winston Ming Wei (2014)
This project is part of an outreach program meant to educate and develop pre-university level students’ interest on the applications of electrical and electronic engineering, particularly in the field of radar systems with a hands-on approach. A short interactive course will also be conducted to allow students to learn and participate in the development of the radar system thereby providing a self-motivating learning experience. Three different modes of the radar operation will be explored and realised through the use of the same circuit set-up and additional add ons in which students can do it themselves with little supervision.